Book Review: Daniel Burrus, The Anticipatory Organisation. Issue 3 (September 2018) - Kumar, Ashok
Daniel Burrus, The Anticipatory Organisation, 2017, Austin, Texas: Greenleaf Book Group Press, 195 pp., US21.95 (Hardbound). ISBN: 978-1-62634-446-4